Modelagem da decomposição e emissão de N20 de resíduos culturais com distinta composição química e quantidade - Chaves, Bruno (2021)
Simulating the dynamics of carbon (C) and nitrogen (N) and nitrous oxide (N2O) emissions during decomposition of crop residues with distinct chemical composition on the soil surface (mulch) is essential to establish strategies to increase soil C stocks and reduce greenhouse gas (GHG) emissions in conservation tillage systems. The objective of the present study was to use the STICS model to: i) interpret the relationship between crop residue quality, location, and soil N content on C and N mineralization (Study 1); to test and improve the model performance in simulating the decomposition dynamics and N2O emissions with the use of two crop residues with different chemical composition and mass added to the soil surface in no-tillage system (Study 2). To achieve these objectives, two datasets were used: i) obtained in a laboratory incubation that evaluated the C and N mineralization of ten crop residues (C:N from 13 to 105) kept on the surface and incorporated into the soil and with and without the addition of N (9 and 77 mg N kg-1 soil); and ii) from a field experiment that evaluated C and N dynamics and N2O emission during decomposition of two crop residues (vetch and wheat) with different chemical composition and mass (3, 6 and 9 Mg DM ha-1). In the study 1, distinct parameters of the STICS decomposition submodule were optimized to describe the dynamics of C and N and to comprehend the effect of N availability on the functional characteristics of soil microbial biomass, allowing to estimate the available N content for surface residue decomposing microorganisms. The parameters CNbio (C:N ratio of microbial biomass), k (decomposition rate of plant residue), h (humification rate of microbial biomass), λ (decomposition rate of microbial biomass) showed significant correlation with the total available N content, defined as the sum of the N content present in the residue (100%) and soil which was 100% for incorporated residues and 24% for surface residues. Decreasing total N availability led to increase CNbio and decreasing k, h, and λ. These results are promising for describing the effects of N availability on C and N mineralization of crop residues. In study 2, the simulation modules for mulch decomposition and N2O emission of STICS were tested and optimized. STICS with its default parameterization failed to simulate decomposition and N2O emission. The simulation of mulch decomposition was improved without the use of contact function, establishing all mulch decomposable regardless of the mass of residue added. N2O emissions were optimized by defining a new function to determine denitrification potential in STICS, based on CO2 emissions to estimate C availability to denitrifiers (Dp = a CO2solo + b CO2res N:Cres). The changes made allowed the STICS model to improve the description of the mulch decomposition dynamics and the magnitude and temporal variability of N2O emissions after residue addition of crop residues with distinct chemical characteristics and mass on the soil surface.